Analisis Komparatif Kinerja Reksa Dana Konvensional dan Syariah pada Periode Krisis dan Non Krisis - Anggriawan Firman, Ananda Oktadino; Wirawan Yasa, Gerianta (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the differences in the performance of conventional and syariah mutual funds in the crisis and non-crisis periods. To measure the performance of mutual funds, the method used is the Sharpe method. The sample in this study was selected using a purposive sampling method. The samples taken in this study is as many as 8 samples of mutual funds consisting of 4 conventional mutual funds and 4 syariah mutual funds in 2008 and 38 samples of mutual funds consisting of 19 conventional mutual funds and 19 syariah mutual funds in 2016. Techniques The analysis used was the Independent Sample T-test. Results of the analysis show that the performance of syariah and conventional mutual funds in 2008 did not differ. In 2016, the results of the Independent T-Test showed that there were differences in performance between syariah and conventional mutual funds. Keywords: Performance, mutual funds, conventional, syariah.